2015
DOI: 10.4238/2015.june.18.2
|View full text |Cite
|
Sign up to set email alerts
|

Partial least squares-based gene expression analysis in preeclampsia

Abstract: ABSTRACT. Preeclampsia is major cause of maternal and fetal morbidity and mortality. Currently, the etiology of preeclampsia is unclear. In this study, we investigated differences in gene expression between preeclampsia patients and controls using partial least squaresbased analysis, which is more suitable than routine analysis. Expression profile data were downloaded from the Gene Expression Omnibus database. A total of 503 genes were found to be differentially expressed, including 248 downregulated genes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…In recent years, the role of ITGB1 in the development of PE has attracted much attention from researchers, and studies have increasingly shown that ITGB1 is involved in regulating the development of PE 10,20 . Through the analysis of differential genes in PE, ITGB1 is downregulated in the placental tissues of PE patients, 9 which is similar to the results of the present study. We found that ITGB1 expression was significantly downregulated in the placental tissues from PE patients, as compared with that of normal pregnant women.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In recent years, the role of ITGB1 in the development of PE has attracted much attention from researchers, and studies have increasingly shown that ITGB1 is involved in regulating the development of PE 10,20 . Through the analysis of differential genes in PE, ITGB1 is downregulated in the placental tissues of PE patients, 9 which is similar to the results of the present study. We found that ITGB1 expression was significantly downregulated in the placental tissues from PE patients, as compared with that of normal pregnant women.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that ITGB1 is involved in the regulation of cell differentiation, proliferation, migration, and other biological behaviors through a unique pathway of signal transduction, 8 and has great functions in mediating cell adhesion and migration. Accumulating evidence demonstrated that ITGB1 expression is downregulated in placental tissues of PE patients, pointing to the potential effect of ITGB1 on PE 9 . Other studies indicated that the function of placental trophoblasts in PE patients could be influenced by the regulation of ITGB1 expression 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies have reported that ITGB1 is related to PE through encoding the beta subunit of integrin. Additionally, up-regulated miR-29b might contribute to PE via its target genes ITGB1 and MCL1[ 35 36 ]. The Mtd/Mcl-1 system plays a crucial role in regulating trophoblast cell functions in both physiological and pathological conditions; Mcl-1 induces apoptosis and reduced proliferation, while Mtd likely shows different properties[ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In placental explants during early pregnancy, hypoxia reduced the expression of SOD1 and increased cell apoptosis ( Kohan-Ghadr et al, 2019 ). Network analysis indicated that JUND and UBB are transcriptional regulators involved in PE ( Jiang et al, 2015 ; Moslehi et al, 2014 ). NFIL3 is essential for normal placental and embryonic development, while SP3 activity is required for normal embryonic development ( Krüger et al, 2007 ; Redhead et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%